Whole-Exome Sequencing Identifies One De Novo Variant in theFGD6Gene in a Thai Family with Autism Spectrum Disorder - Chuphong Thongnak; Areerat Hnoonual; Duangkamol Tangviriyapaiboon; Suchaya Silvilairat; Apichaya Puangpetch; Ekawat Pasomsub; Wasun Chantratita; Pornprot Limprasert; Chonlaphat Sukasem (My University, 2018)
Autism spectrum disorder (ASD) has a strong genetic basis, although the genetics of autism is complex and it is unclear. Genetic testing such as microarray or sequencing was widely used to identify autism markers, but they are unsuccessful in several cases. The objective of this study is to identify causative variants of autism in two Thai families by using whole-exome sequencing technique. Whole-exome sequencing was performed with autism-affected children from two unrelated families. Each sample was sequenced on SOLiD 5500xl Genetic Analyzer system followed by combined bioinformatics pipeline including annotation and filtering process to identify candidate variants. Candidate variants were validated, and the segregation study with other family members was performed using Sanger sequencing. This study identified a possible causative variant for ASD, c.2951G>A, in the FGD6 gene. We demonstrated the potential for ASD genetic variants associated with ASD using whole-exome sequencing and a bioinformatics filtering procedure. These techniques could be useful in identifying possible causative ASD variants, especially in cases in which variants cannot be identified by other techniques.
Keywords: Exome; Autism Spectrum Disorder Research